The complexity of Social Rights in the clinic in Psychology: Material, singular and multidimensional factors - Dall’Igna Ecker, Daniel; Palombini, Analice de Lima (Pensando Psicología, 2020)
Objective: The article is part of the doctoral research that aimed to analyze how the exercise of Social Rights (SR) affects the ongoing subjective and therapeutic processes, in the Psychology clinic, linked to Brazilian public policies. Methodology: Subsidized by records of experiences — 28 clinical cases in therapeutic follow-up, institutional documents, records in the field diary, images, among others — focuses the discussion on the complexity of Social Rights in the clinic in Psychology. Through epistemology and method inspired by post-structuralism, it maps the way in which the SR discourse — education, health, food, work, housing, transportation, leisure, security, social security, maternity and child protection and assistance to the destitute — emerges in the materials and provides elements to think about how the subjects produce and conduct themselves, in life and in therapeutic processes, as subjective beings. Results: In the results, in interlocution with authors from the area, it is proposes three integrated analysis centers: (1) material factors; (2) singular factors; (3) multidimensionality. Conclusions: These centers consider the complexity of the articulation between life, the State, public policies, therapeutic and subjective processes.